MEMBUMIKAN KARAKTER JUJUR DALAM PENDIDIKAN DI ACEH - Teuku Zulkhairi (Islam Futura, 2011)
Significance the study was to prove the importance of grounding the honest character education in Aceh at all levels. This phenomenon is referred to the decadency of morality as a result of the loss of an real culture. That trend of dishonesty spread in the country as which is a direct impact of the failure of the education system in forming the honest character of this nation. In fact, the honesty is the soul of education as well as the purpose of education itself. All education stakeholders should make effort to immediately revive the central role of education in building the character of youth nation who is studying at all levels of education. Grounding honest character of students, besides to save this nation from destruction, it will also supported the success of learners in the path of life and Hereafter